2016
DOI: 10.1177/1548051816630227
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Leader–Member Exchange Relationships and Followers’ Work Performance

Abstract: In this study, we test whether leader political skill moderates the relationship between more transactional leader–member exchange (LMX) relationships and follower work performance. A field study was conducted among 753 followers and 153 leaders from several Norwegian business organizations. The results showed that the negative relationship between more transactional LMX relationships and follower work performance was weaker for employees with a highly politically skilled leader. Thus, leader political skill s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
3
33
0
1
Order By: Relevance
“…We realize, however, that developing SLMX relationships with all followers is not practical because of issues such as span of control, personality differences, differences in background, incongruent values, and so forth (e.g., Buch, Thompson, & Kuvaas, ; Matta & Van Dyne, ). Fortunately, our results imply that there are alternative routes to enabling at least some employee outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We realize, however, that developing SLMX relationships with all followers is not practical because of issues such as span of control, personality differences, differences in background, incongruent values, and so forth (e.g., Buch, Thompson, & Kuvaas, ; Matta & Van Dyne, ). Fortunately, our results imply that there are alternative routes to enabling at least some employee outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell, et al (1990) [9] have supported the above mentioned, as they affirmed that the employee's performance refers to the "observable things people do that are relevant to the goals of the organization" [10]. This reinforces has recommended to the organizations to adopt flexible goals: the flexible goals extend to enhance performance by overcoming self-satisfaction, and devising new ways of thinking, and enhancing energy [11]. Organizational performance has addressed in this as the dependent construct where actually the research problems are occurred.…”
Section: Introductionmentioning
confidence: 89%
“…Dockery and Steiner (1990), for instance, found that follower ability in the initial phase was one of the strongest predictors of leader LMX. Accordingly, a leader's transactional leadership behavior will probably result in an economic LMX relationship with the follower, which in turn has been found to be detrimental to follower behaviors and attitudes (Buch, Martinsen, et al, 2014;Buch, Thompson, & Kuvaas, 2016;Kuvaas et al, 2012). If follower attitudes and behaviors develop negatively as the process unfolds, the leader will, in turn, lack successful experiences that can increase leader self-efficacy as well as information about what leadership behaviors are appropriate and effective to decrease leader ambiguity.…”
Section: Leader Self-efficacy Leader Role Ambiguity and Lmxmentioning
confidence: 99%